2016
DOI: 10.1002/cncr.30036
|View full text |Cite
|
Sign up to set email alerts
|

Peer‐counseling for women newly diagnosed with breast cancer: A randomized community/research collaboration trial

Abstract: Precis:In an RCT, compared to controls, a peer-counseling intervention significantly improved quality of life and maintained marital adjustment in breast cancer patients. Having a peer counselor may prevent or improve psychosocial morbidity following diagnosis. Page 2 of 31 CancerThis article is protected by copyright. All rights reserved. Accepted ArticlePeer Counseling for Breast Cancer 3 Abstract Background: We conducted a randomized trial of peer counseling for newly diagnosed breast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 49 publications
(86 reference statements)
0
42
0
2
Order By: Relevance
“…Six articles examined the efficacy of PN for survivorship, and 5 of them (83%) included breast cancer . Two studies reported that PN interventions significantly improved cancer‐specific well‐being, emotional well‐being, and quality of life .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six articles examined the efficacy of PN for survivorship, and 5 of them (83%) included breast cancer . Two studies reported that PN interventions significantly improved cancer‐specific well‐being, emotional well‐being, and quality of life .…”
Section: Resultsmentioning
confidence: 99%
“…109,118,119 Survivorship Six articles examined the efficacy of PN for survivorship, and 5 of them (83%) included breast cancer. [122][123][124][125][126][127] Two studies reported that PN interventions significantly improved cancer-specific well-being, emotional well-being, and quality of life. 123,124 Other studies showed that PN interventions resulted in higher rates of attendance to medical appointments, lower rates of hospitalization, and fewer intensive care unit admissions and emergency room visits.…”
Section: Treatmentmentioning
confidence: 99%
“…Also, personal peer support contact has been reported to improve wellbeing [12, 15], prepare for recovery [12], and increase self-efficacy [14, 17]. Professionally led peer support groups with health education improved physical, emotional, and social wellbeing as well [10].…”
Section: Introductionmentioning
confidence: 99%
“…Professionally led peer support groups with health education improved physical, emotional, and social wellbeing as well [10]. Peer support has also been associated with more life purpose, less depression [10, 11, 17], fewer breast cancer concerns [17], preserved marital adjustment [15], and better future perspective [17]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation